Specialized knowlwdge of Physics teachers mobilized in rocket launch episodes (Research, Society and Development, 2020)
The teacher's knowledge has been the focus of many scientific researches. In this context, knowing what you are going to teach is part of pedagogical knowledge and content knowledge. In this scenario, there has been a movement of specialization of teaching knowledge, which distances itself from the generalist focus and emphasizes the peculiarities that exist in the teaching of different subjects, including the teaching of Physics. Physics teaching is marked by intense mathematical formulation and the conceptual abstraction of certain contents, which end up correlating with the limitations of the teacher's specialized knowledge to teach. In recent years, artisanal rockets have gained prominence in the discipline of Physics, their contextual and practical approaches take the teaching of Physics beyond mathematical formulations. In this context, our goal is to characterize the specialized knowledge mobilized by physics teachers in an episode report of Rocket Launchings using the theoretical model of Physics Specialized Knowledge of Physics Teachers (PTSK) through a descriptive-analytical methodology. Thus, the results suggest that teaching practices should interpose between pedagogical knowledge and content knowledge, characterized by the specialized knowledge of physics teachers mobilized during the Rocket Launch episode.